Geðheilsa og þjónustunýting hjá einstaklingum með og án sögu um kynferðisofbeldi í æsku sem sækja geðheilbrigðisþjónustu - Rósa Björnsdóttir 1992- (2020)
Numerous studies have examined prevalence rates, correlates and consequences of childhood sexual abuse (CSA), showing that CSA has adverse effects on mental health. Prevalence rates of CSA in the mental health seeking population have been shown to be higher than in the general population and utilization of mental health services of those victimized by CSA seems to be greater. The main aim of the present study was to examine prevalence rates and gender differences of CSA in a diagnostically diverse sample of psychiatric patients seeking mental health services in Iceland. Moreover, the purpose was to examine symptoms of depression, anxiety, stress and post-traumatic stress disorder (PTSD) as well as mental health service utilization of those with and without a history of CSA. Also, the aim was to see whether type and frequency of CSA would have an impact on symptoms of depression, anxiety, stress and PTSD. All participants in this study were seeking mental health services at the psychiatric ward of Landspítali University Hospital of Iceland. Participants were 230 adults, 157 women and 70 men. Results showed that 47% of participants had been victimized by CSA and 58% of women reported CSA. Three quarters (75%) of those reporting CSA met criteria for PTSD according to the PCL-5 (cut-off score ≥33). Furthermore, the effect of type and frequency of CSA was examined with results indicating that those reporting CSA involving intercourse or had been abused frequently were more likely to meet criteria for PTSD (PCL-5 ≥33). Participants who had a history of CSA had more severe symptoms of depression, anxiety and stress compared to participants with no history of CSA. Also, results showed that those victimized frequently by CSA had worse symptoms of depression, anxiety and stress. However, no differences in mental health care utilization between individuals with and without a history of CSA was found in this study. The results underline that CSA is prevalent among those seeking mental health services and mental health ...